1999
DOI: 10.1002/(sici)1097-4547(19991215)58:6<752::aid-jnr3>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Completion of myelin compaction, but not the attachment of oligodendroglial processes triggers K channel clustering

Abstract: The characteristic localization of ion channels is crucial for the propagation of saltatory conduction in myelinated nerves. Voltage-gated Na(+) channels are located at nodes of Ranvier while voltage-gated K(+) channels are mainly found at juxtaparanodal regions. Recently, a humoral factor secreted by oligodendrocytes has been reported to induce clustering of Na(+) channels in CNS axons. However, the molecular mechanisms for K(+) channel clustering as well as the role of oligodendrocytes are still uncertain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…To determine the effect of removal of LIF signaling on myelination in vivo, we examined myelin formation using longitudinal optic nerve sections from LIF knockout (LIF -/- ) mice and wild-type (LIF +/+ ) mice during early postnatal development when myelination is proceeding in mouse optic nerve, P10-P14 (Baba et al,[1999]). To accomplish this, we used MBP and PLP immunoreactivity as myelin markers in the postnatal optic nerve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of removal of LIF signaling on myelination in vivo, we examined myelin formation using longitudinal optic nerve sections from LIF knockout (LIF -/- ) mice and wild-type (LIF +/+ ) mice during early postnatal development when myelination is proceeding in mouse optic nerve, P10-P14 (Baba et al,[1999]). To accomplish this, we used MBP and PLP immunoreactivity as myelin markers in the postnatal optic nerve.…”
Section: Resultsmentioning
confidence: 99%
“…In mouse optic nerves, OPCs that are labeled by an antibody against the NG2 proteoglycan (Levine and Stallcup,[1987]) migrate into optic nerve from the brain through the optic chiasm at about P0, then move toward the retina and reach the boundary of future myelinated and unmyelinated regions at P7 (Baba et al,[1999]). By 10 days of age, MBP-positive myelin sheaths are observed throughout the optic nerves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was found that the PDZ binding domain links Caspr2 to Kv1.1 and Kv1.2 (Poliak et al 2003). Initial reports predicted that PSD-95, a PDZ-containing protein found within the juxtaparanode, might be a potential candidate for this interaction, as it has been shown to associate with Kvβ2; however, later studies reported that PSD-95 and Caspr2 do not interact (Baba et al 1999; Poliak et al 1999). Furthermore, Kv1.1 and Kv1.2 remained clustered at the juxtaparanodes of PSD-95 deficient mice; therefore, it remains to be elucidated what PDZ protein(s) links Caspr2 and Kv channels in the juxtaparanode (Rasband et al 2002).…”
Section: Axonal Domains Of Myelinated Axonsmentioning
confidence: 99%
“…Kv1 channels form macromolecular protein complexes with the cell adhesion molecules (CAMs) Caspr2 and TAG-1, the membrane associated guanylate kinases (MAGUKs) PSD-93 and PSD-95, and the cytoskeletal scaffold 4.1B (Baba et al, 1999; Poliak et al, 1999; Poliak et al, 2001; Traka et al, 2002; Horresh et al, 2008). Juxtaparanodal Kv1 channel clustering depends on CAMs, but not MAGUKs (Rasband et al, 2002; Poliak et al, 2003; Traka et al, 2003; Horresh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%